Rhizobacteria-Mediated Activation of the Fe Deficiency Response in Arabidopsis Roots: Impact on Fe Status and Signaling - Verbon, Eline H.; Trapet, Pauline L.; Kruijs, Sophie; Temple-Boyer-Dury, Coline; Rouwenhorst, T. Gerrit; Pieterse, Corné M. J. (Frontiers in Plant Science, 2019)
The beneficial root-colonizing rhizobacterium Pseudomonas simiae WCS417 stimulates plant growth and induces systemic resistance against a broad spectrum of plant diseases. In Arabidopsis thaliana (Arabidopsis), the root transcriptional response to WCS417 shows significant overlap with the root response to iron (Fe) starvation, including activation of the marker genes MYB72 and IRT1. Here, we investigated how colonization of Arabidopsis roots by WCS417 impacts Fe homeostasis in roots and shoots. Under Fe-sufficient conditions, root colonization by WCS417 induced a transient Fe deficiency response in the root and elevated both the total amount of Fe in the shoot and the shoot fresh weight. When plants were grown under Fe-starvation conditions, WCS417 still promoted plant growth, but did not increase the total amount of Fe, resulting in chlorosis. Thus, increased Fe uptake in response to WCS417 is essential to maintain Fe homeostasis in the more rapidly growing plant. As the WCS417-induced Fe deficiency response is known to require a shoot-derived signal, we tested whether the Fe deficiency response is activated in response to an increased Fe demand in the more rapidly growing shoot. Exogenous application of Fe to the leaves to reduce a potential shoot Fe shortage did not prevent WCS417-mediated induction of the Fe deficiency response in the roots. Moreover, the leaf Fe status-dependent shoot-to-root signaling mutant opt3-2, which is impaired in the phloem-specific Fe transporter OPT3, still up-regulated the Fe deficiency response genes MYB72 and IRT1 in response to WCS417. Collectively, our results suggest that the WCS417-induced Fe deficiency response in the root is controlled by a shoot-to-root signaling system that functions independently of both leaf Fe status and OPT3.